Use of the term "borderline patient" by Swedish psychiatrists. - Burns, T (1986)
Four hundred and sixty seven Swedish psychiatrists (response rate = 52.5%) returned a questionnaire on their understanding of the term "borderline patient". Virtually all had heard of it and 75.2% regularly used it as a diagnosis. Its use was positively associated with female sex, psychotherapy interest and training. 38.8% of the respondents aligned themselves with a predominantly constitutional, and 57.8% with a psychodynamic, understanding of the term. This difference was strongly associated with those diagnoses to which the term was considered equivalent, the symptoms most characteristic of it and with various aspects of the responding psychiatrists' training and work. Swedish psychiatrists emphasized the subjective aspects of the patients' disorder rather than the lability and socially disruptive behaviour which are so prominent in the DSM-III diagnosis. The results of this study underline the urgent need for the establishment of simpler and more practical criteria for the diagnosis.